The Concept of Eschatology in Islam: An Analysis of Fazlur Rahman's Perspective And Al-Munir's Exegesis on Surah Al-Infithar - Humairoh, Siti; Nurwahidin, Nurwahidin; Izdiyan, Mohammad; Wati, Maulida (UI Scholars Hub, 2024)
This paper conducts a profound exploration of eschatology in Islam, with a particular emphasis on the importance of belief in the Day of Judgment from the viewpoints of Fazlur Rahman and Tafsir Al-Munir. The belief system of Muslims is rooted in the Quran and Hadith, with the Five Pillars of Islam and the Pillars of Faith serving as the cornerstone. The fifth pillar of faith enjoins belief in the Day of Judgment, yet regrettably, there exists a lack of awareness among many in this regard. Consequently, this paper presents a comprehensive elucidation of eschatology in Islam, drawing from Quranic verses and contemporary interpretations, notably Tafsir Al-Munir. Adopting an analytical approach, this paper focuses on Surah Al-Infithar, providing an innovative analytical perspective and dispelling potential ambiguities and open-ended concepts. This study employs an interdisciplinary methodology, integrating literature review and contemporary exegesis to depict the significance of belief in the Day of Judgment as a foundational tenet in Islamic faith.